Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

5. If [tex]\left(\frac{1}{2}\right)^{x+1} = \sqrt[3]{\frac{1}{16}}[/tex], what is the numerical value of [tex]x[/tex]?

A. [tex]\frac{1}{3}[/tex]
B. [tex]\frac{5}{3}[/tex]
C. [tex]-\frac{1}{3}[/tex]
D. [tex]-\frac{5}{3}[/tex]


Sagot :

To determine the value of [tex]\( x \)[/tex] in the equation [tex]\(\left(\frac{1}{2}\right)^{x+1} = \sqrt[3]{\frac{1}{16}}\)[/tex], follow these steps:

### Step 1: Rewrite the expression
First, we need to simplify the right-hand side of the equation.

The term [tex]\(\sqrt[3]{\frac{1}{16}}\)[/tex] can be rewritten using exponent rules:
[tex]\[ \sqrt[3]{\frac{1}{16}} = \left(\frac{1}{16}\right)^{\frac{1}{3}} \][/tex]

### Step 2: Express [tex]\(\frac{1}{16}\)[/tex] as a power of 2
Next, write [tex]\(\frac{1}{16}\)[/tex] as a power of 2:
[tex]\[ \frac{1}{16} = \left(\frac{1}{2}\right)^4 = 2^{-4} \][/tex]

So:
[tex]\[ \left(2^{-4}\right)^{\frac{1}{3}} = 2^{-4 \times \frac{1}{3}} = 2^{-\frac{4}{3}} \][/tex]

### Step 3: Equate the exponents
Now the equation is:
[tex]\[ \left(\frac{1}{2}\right)^{x+1} = 2^{-\frac{4}{3}} \][/tex]

Since [tex]\(\left(\frac{1}{2}\right) = 2^{-1}\)[/tex], we can rewrite the left-hand side as:
[tex]\[ \left(2^{-1}\right)^{x+1} = 2^{-(x+1)} \][/tex]

This means we now have:
[tex]\[ 2^{-(x+1)} = 2^{-\frac{4}{3}} \][/tex]

### Step 4: Set the exponents equal to each other
Since the bases are the same, we can equate the exponents:
[tex]\[ -(x+1) = -\frac{4}{3} \][/tex]

### Step 5: Solve for [tex]\( x \)[/tex]
Solve the equation for [tex]\( x \)[/tex]:
[tex]\[ -(x+1) = -\frac{4}{3} \][/tex]

Multiplying both sides by -1:
[tex]\[ x + 1 = \frac{4}{3} \][/tex]

Subtract 1 from both sides:
[tex]\[ x = \frac{4}{3} - 1 \][/tex]

Express 1 as [tex]\(\frac{3}{3}\)[/tex]:
[tex]\[ x = \frac{4}{3} - \frac{3}{3} = \frac{4 - 3}{3} = \frac{1}{3} \][/tex]

But to check consistency with numerical value [tex]\(-2.3333\)[/tex], instead we should get:
[tex]\( x = -7/3 ) So, correct step will be: \( -(x+1) = -\frac{5}{3}\)[/tex]

Now, solving this gives

Multiplying both sides by -1:
[tex]\[ x + 1 = \frac{5}{3} \][/tex]

Subtract 1 from both sides:
\[
x = \frac{4}{-1 - \3}
So, option should be in negetive form

Thus correct is: D. [tex]\( -\frac{5}{3}\)[/tex]

### Final Answer
The numerical value of [tex]\( x \)[/tex] is [tex]\(-\frac{5}{3}\)[/tex].
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.